Zero-Waste Kebaya Design: Integrating the ‘FRANGIPANI’ Method to Enhance Sustainability and Utilize Leftover Lace - Nursari, Faradillah; Simamora M, Regina; Arumsari, Arini (LP2M ISBI Bandung, 2024)
ABSTRACT The kebaya, a traditional Indonesian garment, has evolved to incorporate lace fabric in its design. However, traditional cutting and sewing methods may result in fabric waste, contributing to environmental degradation. Regarding this, the study seeks to develop a zero-waste model for kebaya that utilizes leftover lace, preserving its cultural significance while reducing environmental impact. Thus, the research proposes the FRANGIPANI method, a structured approach consisting of ten systematic stages of the design process that can minimize textile waste and promote sustainability in Kebaya production. This method aims to enhance organization and implementation in the production of kebaya while respecting Indonesia’s rich cultural heritage. The primary goal of this research is to identify a more efficient pre-production system that minimizes textile waste. By focusing on sustainable practices, the research explores the potential for redesigning kebaya into a zero-waste model that utilizes leftover lace, thereby preserving its artistic value while promoting environmental sustainability. Keywords: FRANGIPANI, Kebaya, Lace, Waste, Zero Waste Patter